2007
DOI: 10.1037/0022-0167.54.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to sexual orientation stigma: A comparison of bisexual and lesbian/gay adults.

Abstract: This study extends research on dimensions of sexual minority experience by examining differences between bisexual and lesbian/gay adults in adaptation to sexual orientation stigma. The authors investigated sexual orientation self-disclosure, connection to community, and 4 identity-related variables (internalized homonegativity, stigma sensitivity, identity confusion, and identity superiority) in a community sample of 613 lesbian, gay, and bisexual adults. Sexual orientation effects were found on 3 of these 6 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
424
2
28

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(499 citation statements)
references
References 66 publications
33
424
2
28
Order By: Relevance
“…Herek (2002), for example, found that heterosexuals held more negative attitudes toward bisexuals than toward lesbians or gay men, but negativity and exclusion of bisexuality are also common from lesbian and gay individuals (Greene, 2003). Given a general lack of acceptance, bisexual adults were more likely to report identity confusion, were less likely to disclose their sexual identity, and participated in fewer community activities than lesbians or gay men (Balsam & Mohr, 2007;Lewis et al, 2009). It is possible, that similar feelings of exclusion and lack of belonging are also occurring among bisexual adolescents, and the invisibility of positive role models may be an additive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Herek (2002), for example, found that heterosexuals held more negative attitudes toward bisexuals than toward lesbians or gay men, but negativity and exclusion of bisexuality are also common from lesbian and gay individuals (Greene, 2003). Given a general lack of acceptance, bisexual adults were more likely to report identity confusion, were less likely to disclose their sexual identity, and participated in fewer community activities than lesbians or gay men (Balsam & Mohr, 2007;Lewis et al, 2009). It is possible, that similar feelings of exclusion and lack of belonging are also occurring among bisexual adolescents, and the invisibility of positive role models may be an additive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Es posible que la incongruencia esperada entre el gé-nero y orientación sexual sea menos comprendida en el contexto social de las personas bisexuales (o inseguras) 63 . Además de afrontar con los principios sociales heteronormados que enfrentan gais y lesbianas, las personas bisexuales tienen que luchar contra el complejo estigma-discriminación asociado a la bisexualidad, en particular la negación de esa condición, la necesidad de decidir entre la heterosexualidad y la homosexualidad, dificultades en la construcción de una identidad sexual y menos apoyo social de otras personas no heterosexuales 63,64 . Esta interacción de eventos incrementa la posibilidad de malestar emocional y estrés percibido [63][64][65] .…”
Section: Discussionunclassified
“…Ces résultats renforcent les connaissances actuelles à l'effet que les personnes attirées envers les deux sexes seraient particulièrement susceptibles d'éprouver plus de difficultés dans l'intégration de leur orientation sexuelle (BALSAM;MOHR, 2007;BREG-MAN et al, 2013;HEREK;GILLIS;COGAN, 2009). Plus les jeunes rapportaient avoir réalisé leur différence d'orientation sexuelle il y longtemps, plus faible était leur niveau de dissimulation de l'orientation sexuelle, de confusion d'orientation sexuelle et de difficultés dans le processus d'acceptation, confirmant l'hypothèse de Rosario, Schrimshaw et Hunter (2011) sur le rôle du temps dans l'intégration de l'orientation sexuelle.…”
Section: Variables Sociodémographiquesunclassified
“…Les personnes bisexuelles manifesteraient plus d'attitudes négatives envers elles-mêmes que les gais et lesbiennes (HEREK; GILLIS; COGAN, 2009) et elles rapporteraient une plus grande confusion à l'égard de leur orientation sexuelle (BALSAM;MOHR, 2007;BREG-MAN et al, 2013) ainsi qu'une plus faible probabilité de dévoilement de leur orientation sexuelle (BALSAM;MOHR, 2007). Les travaux menés à ce jour sur les différences garçons-filles dans les niveaux d'homophobie intériorisée et de difficultés d'acceptation de l'orientation sexuelle minoritaire ne sont pas concluants (BALSAM;MOHR, 2007;MORRISON, 2011;PAGE, LINDAHL;MALIK, 2013). L'analyse des écrits disponibles indique en outre que peu d'études portant sur l'intégration de l'orientation sexuelle ont intégré le milieu de résidence dans leurs analyses.…”
Section: Introductionunclassified